Tabung Covid-19: Kita Jaga Kita / Nur Ida Aniza Rusli - Rusli, Nur Ida Aniza (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2021)
FSKM KP, UiTM Negeri Sembilan Kampus Kuala Pilah has organized a donation program named "Tabung COVID-19: Kita Jaga Kita" on 25th September 2020. The main objective of the program is to lessen the burden and to help rural communities living in Kampung Beting who were affected by the pandemic COVID-19. Additionally, this program also aimed to create a spirit of good deeds among UiTM Kuala Pilah staff and also the public community. The fundraising program has been conducted for a week, starting from 9th September to 15th September 2020. Throughout this event, FSKM managed to collect RM520 and received essential items such as thermometers, face masks, and face mask extenders from individual donors.